Design and characteristic analysis of a six‐phase direct‐drive permanent magnet synchronous motor with 60° phase‐belt toroidal winding configuration for electric vehicle. Issue 13 (12th February 2021) - Wei, Yanqi; Si, Jikai; Cheng, Zhiping; Xu, Shuai; Dong, Lianghui; Liang, Jing
Abstract : The six‐phase direct‐drive permanent magnet synchronous motor (DDPMSM) has a good prospect in electric vehicles, ship propulsion, aerospace and other fields due to the advantages of low voltage, high power, low speed and high torque. In this study, a six‐phase DDPMSM is proposed with 60° phase‐belt toroidal winding configuration (60°‐TW). Different from traditional overlapping windings, each coil of 60°‐TW is wound onto the stator yoke in the same direction. The topology of the proposed motor is introduced, and its operation principle is analysed by describing the variation of the magnetic field produced by the six‐phase 60°‐TW versus time. Meanwhile, based on the same power grade and effective volume, the six‐phase PMSM and dual‐three phase PMSM with different winding arrangements are designed. The magnetic field distribution, back‐EMF, cogging torque, torque and loss characteristics are explored in detail. The results show that the proposed six‐phase DDPMSM with 60°‐TW has the characteristics of low speed and high torque in comparison to the traditional six‐phase PMSM and dual‐three phase PMSM, which is expected for direct‐drive systems.